Actividades lúdicas y habilidades motrices básicas en estudiantes de primaria de la Institución Educativa N° 60531 Reverendo Padre Agustin Alcalá Fernández Santa Rita de Castilla 2022 - Rojas Grandez, Katherin Viviana (2024)
The objective of this research was to relate the ludic activities and the basic motor skills in primary students of the Educational Institution N° 60531 Reverend Father Agustín Alcalá Fernández de Santa Rita de Castilla, in response to the question of the problem: What is the relationship between recreational activities and basic motor skills in primary school students of that educational institution? For this, it is used as population and shows 197 students of the school. Being the type of relational research and the study design was field, cross-sectional, and bivariate. For the data collection, the observation technique was considered with two observation guides as instruments, these being validated with due anticipation by experts. The results show that Student's t test statistic= (15,166); with a bilateral significance of 0.000, with a probability of error 0.00%, with a confidence of 95% corroborates that there is a significant association between recreational activities and basic motor skills in primary students of Educational Institution No. 60531 Reverend Father Agustín Alcalá Fernández Santa Rita de Castilla, which proves the study hypothesis.